The Influence of Motivation and Organizational Culture on Employee Performance PT Madubaru PG/PS Madukismo - Dedi Ristanto; Bangun Putra Prasetya (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This research examines (1) motivation on employee performance at PT Madubaru PG/PS Madukismo, (2) organizational culture on employee performance at PT Madubaru PG/PS Madukismo, and (3) motivation that determines employee performance and the influence of organizational culture. At PT Madubaru PG/PS Madukismo. This research will study cause and effect relationships using a quantitative approach. This research is classified as survey research whose research instrument is a questionnaire. The sample for this research consisted of 120 employees from all departments of PT Madubaru PG/PS Madukismo. The sampling technique used was proportional sampling. Data was collected using a questionnaire which was tested for validity and reliability. The data analysis technique used is multiple regression. The test results state: (1) motivation has a positive and significant effect on the performance of PT Madubaru PG/PS Madukismo employees. It can be seen that the beta coefficient (β) is 0.135 (p=0.039) and contributes to the influence of motivation on employee performance at PT Madubaru PG/PS Madukismo of (∆R2) 0.045; (2) organizational culture has a positive and significant effect on the performance of PT Madubaru PG/PS Madukismo employees. It can be seen from the beta coefficient (β) of 0.281 (p=0.003) and the contribution of organizational culture to employee performance at PT Madubaru PG/PS Madukismo of (∆R2) 0.090; and (3) motivation and organizational culture have a positive and significant influence on the performance of PT Madukismo employees. It can be seen using the statistical results of the regression test that motivation with a beta coefficient (β) of 0.276 (p=0.024) and organizational culture (β) of 0.123 (p=0.003) have a positive and significant effect on employee performance. The contribution of the influence of motivation and organizational culture on employee performance is (∆R2) 0.085 (8.5%) and the rest are other variables.